Shear Wave Wavefront Mapping Using Ultrasound Color Flow Imaging. (October 2015) - Yamakoshi, Yoshiki; Kasahara, Toshihiro; Iijima, Tomohiro; Yuminaka, Yasushi
A wavefront reconstruction method for a continuous shear wave is proposed. The method uses ultrasound color flow imaging (CFI) to detect the shear wave's wavefront. When the shear wave vibration frequency satisfies the required frequency condition and the displacement amplitude satisfies the displacement amplitude condition, zero and maximum flow velocities appear at the shear wave vibration phases of zero and π rad, respectively. These specific flow velocities produce the shear wave's wavefront map in CFI. An important feature of this method is that the shear wave propagation is observed in real time without addition of extra functions to the ultrasound imaging system. The experiments are performed using a 6.5 MHz CFI system. The shear wave is excited by a multilayer piezoelectric actuator. In a phantom experiment, the shear wave velocities estimated using the proposed method and those estimated using a system based on displacement measurement show good agreement.